Проблема підвищення працездатності ненапружених шпонкових з'єднань - Гайдамака, Анатолій Володимирович; Музикін, Юрій Дмитрович; Кулик, Геннадій Григорович; Бородін, Дмитро Юрійович (Національний технічний університет "Харківський політехнічний інститут", 2022)
Для уникнення економічних втрат виробництва через зупинки щодо проведення ремонтних робіт виникає необхідність дослідження з розробкою заходів підвищення їх надійності. Було проведено відповідний аналіз літератури з метою пошуку напрямків методів підвищення працездатності шпонкових з’єднань. В роботі проаналізовано особливості праці найбільш поширених ненапружених з'єднань призматичними шпонками. Аналіз стану експлуатації ненапружених шпонкових з'єднань, напрямків удосконалення їх конструкцій та сучасного спрощеного методу розрахунку пояснює актуальність досліджень працездатності і підвищення надійності. Розглянуто шляхи підвищення надійності з’єднань призматичними шпонками. В цій роботі виконано огляд деяких останніх найбільш цікавих, на думку авторів, досліджень з контактної взаємодії деталей. Сформульовано вимоги щодо розробки і дослідження нових шпонкових з'єднань. За базову прийнято конструкцію з’єднання з циліндричними робочими поверхнями шпонки. Проаналізовано відомі методи визначення контактних деформацій різними науковими школами. Сформульовано вимоги щодо розвитку методу розрахунку ненапружених шпонкових з'єднань. За базовий прийнято метод наукової школи Волгоградського державного технічного університету.

This paper reports the location of stress concentration and compares the results obtained by theoretical analysis with the analysis done by the analysis software. In order to avoid economic losses of production due to stoppages related to repair work, there is a need to study the development of measures to increase their reliability. Despite knowing the importance of this a very little research work has been reported in this field. An appropriate analysis ind directions for improving methods performance of keyed joints. The paper analyzes the features of the work of the most common non-stressed connections prismatic keys. Analysis of the state of operation of non-stressed keyed joints, directions for improving their designs, and modern simplified method of calculation explains the relevance of studies of workability and reliability improvement. Ways have been considered to increase the reliability of connections with prismatic keys. In this work, a review of some of the latest, most interesting, by the author's opinion, is carried out, studies on the contact interaction of parts. The requirements for the development and research of new keyed joints are formulated. The basic design of the connection with cylindrical working surfaces of the key is adopted. Known methods of determination are analyzed contact deformations by various scientific schools. The requirements for the development of the method of calculating unstressed keyways are formulated connections. All our calculations were primarily made based on the method of the Scientific School of Volgograd State Technical University and it was adopted as the basic one.
The problem of productivity increase of the unstressed keyways joints
Keywords: удосконалення конструкції; ненапружені шпонкові з'єднання; самозаклинювання шпонки; шпонкове з’єднання циліндричним сегментом; контактні деформації; contact deformation; self-locking of the key; non-stressed keyed connections; improvement of the design; unstressed keyed connections